PSYCHOLOGICAL REALISM IN ENGLISH AND UZBEK LITERARY TRADITIONS - Djalaldinova Malohat Zuxurdinovna (TADQIQOTLAR, 2026)
Abstract This article examines the artistic interpretation of psychological realism within the landscapes of the human psyche, tracing the evolution of realism and its psychologically oriented dimension in world and Uzbek literature. Realism, which emerged in the nineteenth century as a reaction against Romanticism, sought to depict life with verisimilitude, objectivity, and socio-historical precision. Psychological realism developed as one of its most intricate branches, foregrounding the inner mechanisms of consciousness, emotional experience, and cognitive processes. Drawing on examples from the works of Fyodor Dostoevsky, Henry James, Virginia Woolf, Marcel Proust, James Joyce, and William Faulkner, the study explores narrative strategies such as interior monologue and stream of consciousness as aesthetic instruments for representing subjective experience. It further analyzes the development of psychological realism in Uzbek literature through the prose of Abdulla Qodiriy, Cho‘lpon, and Asqad Muxtor, demonstrating how psychological inquiry became central to the artistic exploration of identity, moral conflict, and social transformation.